Pengajaran interaktif berasaskan arahan berbantukan komputer (CAI): pakej pengajaran untuk proses pembuatan bahan plastik - Ahmad Baharuddin Abdullah; Ainol Syakina Mohd Radhi (2007)
Computer-based instructional materials offer great potential to enhance learning effectiveness including engineering discipline. Using readily available development software, sophisticated graphics, animations and videos can be created to present engineering topics in ways that are not possible within the conﬁnes of the traditional textbook and lecture format. This article presents an instructional media (package) which is developed to assist in teaching of processing of plastics course. This example includes lecture supplements, colorful and animated pictures, interactive example problems, videos and interactive computer applications. Using animations, videos, graphics and interactivity, the instructional media is designed to engage and stimulate students, to effectively explain and illustrate course topics and to increase student involvement in the class